PELATIHAN PENYUSUNAN LAPORAN KEUANGAN UMKM (USAHA MIKRO, KECIL DAN MENENGAH) PADA DESA BINAAN LUMBAN PEA TIMUR KECAMATAN BALIGE KABUPATEN TOBA - Thomas Sumarsan Goh; Dimita H. P. Purba; Duma M. Elisabeth; Ivo M. Silitonga; Wesly A. Simanjuntak; Hotlan Butar-Butar; Jatongam Nainggolan; Arison Nainggolan; Rahel Junita; Eva Julia G. Harianja; Sahala Purba; Januardi Mesakh; Fati G. N. Larosa; Tri Darma Sipayung; Rimky M. P. Simanjuntak (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
The Service Team in collaboration with the Lumban Pea Timur, Kabupaten Toba, helps MSME actors in improving and developing their products through a marketing approach, recording transactions clearly, completely and correctly, so that in the end MSME actors can carry out their business activities. As a benefit of this assistance, in the form of cooperation carried out by two institutions, namely MSME actors will benefit from knowledge and skills to increase sales and record transactions that are useful for decision making. For the Service Team, it will add relationships and understanding of community business activities.